MINOR AND MAJOR SYNTAX: AN EXPLORATION OF PHRASE AND SENTENCE STRUCTURE - Teshaboyeva Nafisa Zubaydulla qizi; Xidirova Dilnoza Nurali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article delves into the distinction between minor and major syntax within linguistic theory, focusing on their application in phrase and sentence structures. Minor syntax encompasses the formation of smaller linguistic units that lack full syntactic independence, while major syntax involves the construction of grammatically complete sentences. The discussion highlights the fundamental categories of syntax: phrases and sentences, analyzing their roles in language comprehension and production.